Answer:
64
Step-by-step explanation:
4 * 4 * 4 = 64
The answer is A because it is
Answer:
sorry I didn't know mark as btaiblist
Answer: 23%
Step-by-step explanation: just is rate me good bye
Answer:
Step-by-step explanation:
Given that:
![f(x) = x^3 + x - 3 = 0](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E3%20%2B%20x%20-%203%20%3D%200)
Since the given function is equal to zero, then the function :
![f(x) = x^3 + x - 3](https://tex.z-dn.net/?f=f%28x%29%20%3D%20x%5E3%20%2B%20x%20-%203)
where;
and
![x = 2](https://tex.z-dn.net/?f=x%20%3D%202)
![f(x) = (1)^3 + (1) - 3 \\ \\ f(x) = 1 + 1 - 3 \\ \\f(x) = -1 < 0](https://tex.z-dn.net/?f=f%28x%29%20%3D%20%281%29%5E3%20%2B%20%281%29%20-%203%20%5C%5C%20%20%5C%5C%20f%28x%29%20%3D%201%20%2B%201%20-%203%20%5C%5C%20%5C%5Cf%28x%29%20%3D%20-1%20%3C%200)
![f(2) = x^3 + x - 3 \\ \\f(2) = (2)^3 + 3 - 3 \\ \\f(2) = 8 + 3 - 3 \\ \\f(2) = 11 - 3 \\ \\f(2) = 8 > 0 \\ \\](https://tex.z-dn.net/?f=f%282%29%20%3D%20%20x%5E3%20%2B%20x%20-%203%20%5C%5C%20%5C%5Cf%282%29%20%3D%20%282%29%5E3%20%2B%203%20-%203%20%20%5C%5C%20%5C%5Cf%282%29%20%3D%208%20%2B%203%20-%203%20%20%5C%5C%20%5C%5Cf%282%29%20%3D%2011%20-%203%20%5C%5C%20%5C%5Cf%282%29%20%3D%208%20%3E%200%20%5C%5C%20%5C%5C)
Thus; f(1) < 0 and f(2) > 0